Children's Rights Must Be Fulfilled by Parents From an Islamic Perspective - M. Farid As Siddik (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2023)
This study aims to find out and describe the rights of children that parents must fulfill in the Islamic view because children are a mandate given by the Divine to both parents. A child means hope for the future, not just a connector of offspring but also as a successor to dreams and struggles. The type of research used is in the form of library studies (Library Research). A literature study is used in collecting information and data with the help of various library materials, such as documents, books, magazines, and historical stories. Meanwhile, the approach used by researchers is a descriptive qualitative approach. The results of this study show that in this life, two things must be understood and fulfilled by every human being, namely, an understanding of what is called rights and an understanding of obligations. The rights of the child that the parents are obliged to fulfill can be grouped; into 1) the rights of the child before birth and 2) the rights of the child when born.